Kanaka 'Ōiwi Methodologies : Moʹolelo and Metaphor - Oliveira, Katrina-Ann R. Kapa'anaokalaokeola Nakoa; Wright, Erin Kahunawaika'ala (University of Hawaiʹi Press, 2015)
For many new Indigenous scholars, the start of academic research can be an experience rife with conflict in many dimensions. Though there are a multitude of approaches to research and inquiry, many of those methods ignore ancient wisdom and traditions as well as alternative worldviews and avenues for both discovery and learning. The fourth volume in the Hawai'inuiākea series, guest coedited by Katrina-Ann R. Kapā'anaokalāokeola Nākoa Oliveira and Erin Kahunawaika'ala Wright, explores techniques for inquiry through some of the many perspectives of Kanaka 'Ōiwi (Native Hawaiian) scholars at work today. Kanaka 'Ōiwi Methodologies: Mo'olelo and Metaphor is a collection of "methods-focused" essays written by Kanaka scholars across academic disciplines. To better illustrate for practitioners how to use research for deeper understanding, positive social change, as well as language and cultural revitalization, the texts examine Native Hawaiian Critical Race Theory, Hawaiian traditions and protocol in environmental research, using mele (song) for program evaluation, and more.